2001
DOI: 10.1049/ip-opt:20010602
|View full text |Cite
|
Sign up to set email alerts
|

All optical signal regeneration in cascaded Mach–Zehnder interferometer wavelength converter

Abstract: the XPM wavelength converter is very useful for an efficient optical wavelength conversion, because it enables an increase in the input-dynamic range and accommodates a relatively small input of optical power. ACKNOWLEDGMENT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…It shows high conversion efficiency, extinction ratio enhancement, and negative chirp characteristics. Moreover, we showed that the XPM wavelength converter has an advantage of all optical regeneration by using very steep transfer curves (Lee et al 2001).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…It shows high conversion efficiency, extinction ratio enhancement, and negative chirp characteristics. Moreover, we showed that the XPM wavelength converter has an advantage of all optical regeneration by using very steep transfer curves (Lee et al 2001).…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, using current control and CW holding beam power control in preamplifier give advantages such as uniform power level of wavelength converted output signal, higher ER and very steep slope of transfer function. So, we can expect that 2R regeneration of wavelength converted signal using these steep transfer curve (Lee et al 2001). However, in case of the current control method, the input signal is distorted seriously (under-shooting or over-shooting) during amplifying process by the preamplifier in proportion to data bit rate.…”
Section: Xpm Wavelength Converter Integrated With Preamplifiermentioning
confidence: 99%
“…In spite of extensive experimental approaches, only a few attempts have been reported for analytical analyses [1,2,3,4,5], but the former analytical approaches lack either strictness or simplicity. For example, Refs.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Ref. 2 shows more strict calculations that are based on the first principle of the device physics, although the calculations are much more complicated and hence would be time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the XPM wavelength converter has an advantage of all-optical regeneration using very steep transfer curves. 7 However, the XPM wavelength converter has a critical drawback of limited the input power dynamic range ͑IPDR͒, i.e., 3 to 4 dB at 10 Gbps operation. The IPDR is important because the signals are experiencing the different attenuation through the network with subsequent variations of the input power to the switch blocks.…”
Section: Introductionmentioning
confidence: 99%